2016
DOI: 10.1007/s10286-016-0363-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefit of midodrine hydrochloride in symptomatic orthostatic hypotension: a phase 4, double-blind, placebo-controlled, randomized, tilt-table study

Abstract: ObjectiveMidodrine hydrochloride is a short-acting pressor agent that raises blood pressure in the upright position in patients with orthostatic hypotension. The US Food and Drug Administration’s Subpart H approval, under which midodrine was initially approved, requires post-marketing studies to confirm midodrine’s clinical benefit in this indication. The purpose of this study was to evaluate the clinical benefit of midodrine with regard to symptom response.MethodsThis was a double-blind, placebo-controlled, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 23 publications
0
33
0
2
Order By: Relevance
“…Trials were randomized, double blind, and parallel‐design, and they enrolled patients with OH of different etiologies with supine‐to‐standing fall of systolic BP of at least 15 mm Hg accompanied by at least moderate dizziness/lightheadedness. A phase IV randomized, double‐blind, placebo‐controlled trial confirmed that midodrine also improves symptoms of OH …”
Section: Management Of Neurogenic Orthostatic Hypotensionmentioning
confidence: 94%
See 1 more Smart Citation
“…Trials were randomized, double blind, and parallel‐design, and they enrolled patients with OH of different etiologies with supine‐to‐standing fall of systolic BP of at least 15 mm Hg accompanied by at least moderate dizziness/lightheadedness. A phase IV randomized, double‐blind, placebo‐controlled trial confirmed that midodrine also improves symptoms of OH …”
Section: Management Of Neurogenic Orthostatic Hypotensionmentioning
confidence: 94%
“…A phase IV randomized, double-blind, placebocontrolled trial confirmed that midodrine also improves symptoms of OH. 62 Administration of midodrine raises standing, sitting, and supine systolic and diastolic BP in patients with nOH. Standing systolic BP increases by 10 mm Hg to 30 mm Hg 1 h after a 10-mg dose of midodrine, with some effect persisting for 2 to 3 h. Treatment should begin with a 2.5-or 5-mg dose, which can then be increased up to 10 mg to be taken up to 3 times a day.…”
Section: Midodrinementioning
confidence: 99%
“…Indeed, a phase 4 tilt-table placebo-controlled trial with midodrine used time to symptoms of syncope or presyncope during passive head-up tilt as the main outcome measure. 41 As discussed earlier, this is a patient-reported outcome that represents a straightforward functional improvement.…”
Section: Syncope Presyncope and Fallsmentioning
confidence: 83%
“…Finally, some trials of nOH used the "time to symptoms after standing" as a patient-reported endpoint. 41 The primary outcome was the time since the tilt table is positioned in the 60-degree angle until the patient experiences symptoms of syncope or near syncope and asks to be tilted down. This endpoint has obvious advantages.…”
Section: Objective Outcome Measures For Clinical Trials Of Neurogenicmentioning
confidence: 99%
“…Allerdings ist Midodrin auch mit dem Auftreten einer Liegendhypertonie assoziiert und wird daher nicht bei Patienten empfohlen, die vor Beginn der Therapie im Liegen einen Blutdruck von über 170 mm Hg systolisch aufweisen. Wirksam ist Midodrin nahezu unabhängig von der, der orthostatischen Hypotonie zugrunde liegende Erkrankung [37]. ▶tab 2 Medikamente, die eine orthostatische Hypotonie auslösen oder verschlechtern können (basiert auf [33]…”
Section: Pharmakotherapie Der Orthostatischen Hypotonieunclassified